Nonhydrolytic sol-gel synthesized oligosiloxane resin reinforced thiol-ene photocured coatings for the immobilization of acetylcholinesterase - ÇAKMAKÇI, EMRAH; DEMİR, SERAP (SPRINGER, 2019)
Acetylcholinesterase (AChE), which is responsible for the hydrolysis of neurotransmitter acetylcholine, is a critical enzyme for the nervous system and also a biomarker for organophosphorous pesticide detection. The immobilization of AChE is an active area of research and recently the use of sol-gel-derived materials for enzyme immobilization has gained a lot of attraction. In this work, AChE was covalently immobilized onto a photocured substrate which was reinforced with an oligosiloxane resin. The oligosiloxane resin was designed to have both vinyl and epoxide groups and prepared via nonhydrolytic sol-gel technique. The strategy employed in this study offered a platform that has good mechanical and thermal properties and also suitable for modification. Thus, AChE was also immobilized onto these substrates after amine modification of the epoxy groups and followed by glutaraldehyde activation. Over 80% enzyme immobilization yield was achieved. At certain pH values (5.5 and 8.5) and under relatively higher temperatures (above 40 degrees C) the immobilized enzymes were found to have higher catalytic activity than the free enzyme. Furthermore, by immobilization the reuse and the storage stability of the enzyme was improved and the stability of the immobilized enzyme against the inhibitory effects of certain metal cations was enhanced [GRAPHICS] . Nonhydrolytic sol-gel synthesized oligosiloxane resin reinforced thiol-ene photocured coatings for the immobilization of acetylcholinesterase. Emrah CAKMAKCI, Serap DEMIR. HighlightsAn oligosiloxane resin was prepared via nonhydrolytic sol-gel technique.The oligosiloxane resin was used to reinforce thiol-ene photocured coatings.Acetylcholinesterase was immobilized onto the photocured coatings.By immobilization, storage stability, reuse and metal ion resistance were improved.
Keywords: Thiol-ene; Nonhydrolitic sol-gel; Acetylcholinesterase; Enzyme immobilization; COVALENT IMMOBILIZATION; PASSIVATION LAYER; ALPHA-AMYLASE; FUNCTIONALIZATION; MEMBRANES; LIPASE; EPOXY